Peran Lembaga Kesejahteraan Sosial Anak (LKSA) Siti Fatimah dalam Memberikan Pelayanan Kesejahteraan Sosial terhadap Anak di Desa Nogosari Kecamatan Pandaan Kabupaten Pasuruan - Rizki, Surya Alivia; Suma, Nasobi Niki (Al-I'timad: Jurnal Dakwah dan Pengembangan Masyarakat Islam, 2025)
Child welfare services are a form of empowerment to protect and improve the quality of life of children, especially through the Siti Fatimah Child Social Welfare Institution (LKSA) in Pandaan District, Pasuruan Regency. This institution serves neglected children, orphans, school dropouts, and children from troubled families. This study aims to determine the role and supporting factors of LKSA Siti Fatimah in providing social welfare services to children in Nogosari Village. Using a descriptive qualitative approach, data was obtained through observation, interviews, and documentation. The results showed that LKSA has a role as a facilitator, motivator, mediator, and dynamator in empowerment programs covering the fields of education, social, skills, spirituality, and entrepreneurship. Supporting factors include the availability of infrastructure, community support, donors, and motivation from managers. The obstacles faced include children's personalities, low community awareness, and limited funding.